Digital Student in Modern School - Discussion About the Current State of Education - Grażyna Penkowska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The term "information overload", which Alvin Toffler used in his book "Future Shock" first published in 1970, was futuristic (A. Toffler, s. 316). Now the utopian vision of Toffler has materialized. These are modern information and communication technologies that play a significant role in building up the phenomenon of information overload. The problem is how modern education should change, and where to draw the line at including new technologies in students' work. The article contains a discussion about the diagnosis of information overload and an attempt to place the teacher in the digital world. Today's students overuse modern technology, which does not always result in better quality education.